Continuous low‐dose gemcitabine in primary cutaneous T cell lymphoma: A retrospective study. Issue 6 (11th April 2022) - Di Raimondo, Cosimo; Vaccarini, Sara; Nunzi, Andrea; Rapisarda, Vito; Zizzari, Annagiulia; Meconi, Federico; Monopoli, Alessandro; Narducci, Maria Grazia; Scala, Enrico; Bianchi, Luca; Tesei, Cristiano; Cantonetti, Maria
Abstract: The aim of our retrospective study was to evaluate the efficacy of a continuous therapy with a lower dosage of gemcitabine compared to those usually administered in patients with cutaneous T cell lymphomas (CTCL). Twenty‐two patients received different dosages of gemcitabine. Dosage and schedule of the drug were chosen on the basis of clinical features. Gemcitabine was given at 1000 mg every 15 days in 13 patients (four mycosis fungoides [MF], nine Sezary syndrome [SS]); at 1000 mg at days +1, +8, +15 in six cases (three MF, three SS). All patients had been previously treated: four patients had received both skin directed and systemic treatments. Eighteen patients had received photopheresis, IFN, chemotherapy and immunotherapy. The objective response rate (CR + PR) among all patients was 54.5% (12 of 22 patients) with a CR of 4.5% (one of 22 patients) and a PR of 50% (11 of 22 patients). Patients with SS had an ORR of 61.5% (eight of 13 patients) with one CR (7%) and seven PR (53.8%); patients with MF showed an ORR of 55.6% (five of nine patients) but no patients experienced CR (0%). The schedule with the highest efficacy and the lowest toxicity profile was 1000 mg every 15 days. Median progression free survival and overall survival in all patients were 17 and 45 months respectively. Gemcitabine was generally well tolerated. We have demonstrated that a much lower dose of gemcitabine (1000 mg once every 15 days) in patients with advanced‐stage and refractory CTCL can lead to a durable response, with tolerable and manageable adverse effects.